Fundamentals of electromagnetism : vacuum electrodynamics media and relativity - Lopez A Davalos (Argentina Springer Publications, 2023)
This textbook is a revised and enlarged version of notes for a one-semester course on electromagnetism. It covers the theory of electromagnetic phenomena in vacuum and in material media. The book includes a CD-ROM with didactic software, to solve boundary value problems in electrostatics and magnetostatics.
Keywords: Electricity and electronics